THE CONCEPT OF THE IDEAL LEADER IN NAJIB KAILANI'S NOVEL AN-NIDĀUL KHĀLID: MICHAEL RIFFATERRE'S SEMIOTIC ANALYSIS - Qurratul Aini (Arabic Literature Department, 2021)
A leader is someone who is elected by the community for the common good. The concept of a leader includes not only those who hold positions in the government system, but also religious leaders.. This study aims to describe the ideal leader in Najib Kailani's An-Nida@ul Kha@lid novel by using Michael Riffaterre's semiotics as an analytical tool. The method used in this research is descriptive qualitative analysis by describing the data in accordance with what it is then followed by analysis. The data collection technique is using listening and note-taking techniques. The results of this study state that the concept of an ideal leader must comply with three things, namely: 1) The leader must be wise making decisions, 2) the leader must defend the interests and unite the people, and 3) the leader must accommodate the aspirations of the people. While, the matrix in the text is the concept of an ideal leader who has a model of nurturing and embracing the community, and a variant in the form of a text related to ideal leadership. The potential hypogram found in the text is the same as the matrix, namely the concept of an ideal leader, while the actual hypogram, departs from the true story experienced by the author, where he grew and developed along with the outbreak of World War II, then in 1958-19865 went in and out of prison, and In 1982, the novel An-Nidaul Khalid was published. Keywords: Ideal Leader Concept, Semiotic, Riffaterre, Novel, Najib Kailani